The socio-economic approach to the study of main economic systems. Socialism and capitalism. Part 1 = Społeczno-ekonomiczne podejście do badań głównych systemów gospodarczych. Socjalizm i kapitalizm. Część 1. - Akulich, Maria; Kaźmierczyk, Jerzy (Zielona Góra: Faculty of Economics and Management Press)
Society is explored with the help of various approaches and methods that allow us to analyze the economy, politics, culture and society. Society as a socio-economic system can be effectively studied from the standpoint of the socio-economic approach, which is implemented within the framework of the formational approach. It was formerly used e.g. by Daniel Bell, John Kenneth Galbraith, Karl Marx, Leonid Weger, Yoshihiro Francis Fukuyama, Erik Olin Wright, and Immanuel Maurice Wallerstein.
Keywords: socjalizm; kapitalizm; post-kapitalizm; globalizacja; socialism; capitalism; post-capitalism; globalization